Enhancing the hepatitis B care cascade in Australia: A cost‐effectiveness model. Issue 5 (3rd January 2020) - Xiao, Yinzong; Howell, Jessica; van Gemert, Caroline; Thompson, Alexander J.; Seaman, Christopher P.; McCulloch, Karen; Scott, Nick; Hellard, Margaret E.
Abstract: If Australia is to successfully eliminate hepatitis B as a public health threat, it will need to enhance the chronic hepatitis B (CHB) care cascade. This study used a Markov model to assess the impact, cost and cost‐effectiveness of scaling up CHB diagnosis, linkage to care and treatment to reach national and international elimination targets for hepatitis B in Australia. Compared to continued current trends, the model calculated the difference in care cascade projection, disability‐adjusted life years (DALYs), costs and the incremental cost‐effectiveness ratio (ICER), of scaling up CHB diagnosis, linkage to care and treatment to reach: (a) Australia's 2022 national targets and (b) the WHO's 2030 global targets. Achieving the national and WHO targets had ICERs of A13 435 (A10 236‐A21 165) and A14 482 (A13 031‐A25 641) per DALY averted between 2016 and 2030 in Australia, respectively. However, this excluded implementation and demand generation costs. The ICER for the National Strategy and WHO Strategy remained under A50 000 per DALY averted if Australia spent up to A328 or A538 million, respectively, per annum (for 2016‐2030) on implementation and demand generation activities. Sensitivity analysis showed that cost‐effectiveness was predominately driven by the cost of CHB treatment and influenced by disease progression rates. Hence for Australia to reach the National Hepatitis B Strategy 2022 targets and WHO Strategy 2030 targets, it requires an improvement in the CHB care cascade. We estimated it is cost‐effective to spend up to A328 million or A538 million per year to reach the National and WHO Strategy targets, respectively.